Supplementing taurine to plant-based diets improves lipid digestive capacity and amino acid retention of Senegalese sole (Solea senegalensis) juveniles - Richard, Nadège (2019)
Recent studies reported positive effects of taurine supplementation to plant protein-based diets on fish growth performance and feed conversion ratio but the mechanisms involved remain unclear. The objective of this work was to provide a first insight on the importance of taurine on dietary protein and lipid absorption and utilisation, in Senegalese sole (Solea senegalensis) juveniles fed plant-based diets. Seven practical diets were tested: a fishmeal-based diet (FM) and a plant protein-based formula (PP85) to which taurine was added in graded levels: 0.2% (TAU1), 0.3% (TAU2), 0.4% (TAUS), 0.7% (TAU4) and 1.5% (TAU5). Short-term metabolic trials were performed by tube-feeding the different experimental diets labelled with different tracers: C-14-taurine, C-14-triolein (as tracer of dietary triacylglycerol) and a mixture of C-14-amino acids. Feeding sole juveniles with the PP85 diet affected taurine metabolism, since a higher proportion of dietary taurine was directed to gallbladder and probably used for bile salt synthesis. Consistent with this, fish receiving the plant-based low taurine-content diets (PP85 and TAU1) displayed a poor triacyglycerol digestion capacity. A higher proportion of C-14-amino acids was retained in fish muscle when fed the TAU5 compared to the PP85 diet. These short-term trials suggested that taurine supplementation to a plant-based diet might be beneficial to sole performance by enhancing bile salt synthesis and triacylglycerol digestion as well as muscle amino acid retention. However, this dietary supplementation should be tested in long-term trials to verify the effect on fish growth and to assess the beneficial effects on protein and lipid metabolism suggested here. Statement of relevance in the general field of aquaculture (limited to 60 characters): Adding taurine to a plant-based diet is beneficial for sole (C) 2016 Elsevier B.V. All rights reserved.